THE ROLE OF CALCIUM HYDROXYAPATITE IN STIMULATING COLLAGEN PRODUCTION AND IMPROVING SKIN QUALITY IN AESTHETIC TREATMENTS: AN INTEGRATIVE REVIEW - Driessen, Rayza Rafaella Melniski; Locatelli, Claudriana; Veiga , Natan; da Silva, Eduardo Sttocco; de Souza, Julia Tristão; Luz, Karine (Seven Editora, 2024)
With the incessant search for different aesthetic procedures to minimize the effects of aging, it becomes necessary to increase research on the effects, improvements, and methods of skin care. Scientific evidence was then sought on the functioning of calcium hydroxyapatite in stimulating collagen production and improving skin quality in the treatments involved. To this end, an integrative review was used, and the search was carried out in the PubMed and Virtual Health Library (VHL) databases. The descriptors used were: calcium hydroxyapatite and dermal filler and collagen. A total of 61 articles were found, of which 14 met the inclusion criteria in the research. It was noticed that the dual action of the biostimulator, which acts both as an immediate filling agent and as a long-term collagen stimulator, highlights its effectiveness in improving skin quality and obtaining long-lasting and natural results in the context of facial rejuvenation. DOI:https://doi.org/10.56238/sevened2024.037-040